S29 A randomised controlled trial of over the counter medicine CS1002 for acute cough. (15th November 2016) - Birring, SS; Brew, J; Kilbourn, T; Morice, AH
Abstract : Introduction: CS1002 contains diphenhydramine/ammonium-chloride/levomenthol in a demulcent preparation. We conducted a randomised controlled trial to compare the efficacy of CS1002 with Bell's Simple Linctus (BSL). Methods: 163 subjects with acute cough associated with upper respiratory tract infection, URTI (onset ≤7 days and cough severity VAS ≥60 mm), presenting to pharmacists (64%) or general practitioners were randomised to CS1002 or BSL. The subjects (mean age 39 years, 57% female) were instructed to take their medication four times daily (5/5/10/10 ml) for 7 days or until resolution. Investigators were blinded to the treatment allocation. The primary analysis, cough severity VAS (0–100) was ANCOVA in an intention to treat population. Results: CS1002 (n = 82) compared to BSL (n = 75), after 3 days, was associated with a greater reduction in cough severity (adjusted mean(SE) difference 5.9 (4.3), p = 0.18), cough sleep disruption VAS (mean diff 11.6 (4.5), p = 0.01) and cough frequency VAS (mean diff 8.1 (4.1), p = 0.05, Figure 1 ). There was a greater improvement in QOL (LCQ-acute) with CS1002 compared to BSL after 5 days; mean diff 1.2 (0.6), p = 0.04. The reduction in cough severity with CS1002 was similar in dry/chesty/tickly categories of cough. Cough resolved after 3 days in 24.4% of CS1002 subjects compared to 10.7% BSL, p = 0.02. CS1002 was well tolerated, similar to BSL. In conclusion: We have conducted the largest RCT in URTI with validated outcome measures. CS1002 reduced the impact of cough associated with URTI with a greater reduction in cough frequency and sleep disruption and improvement in QOL and cough resolution compared to BSL.